Voluntary Staff Turnover In A Leisure Industry: The Role Of A Human Resource Department - Lin, Chan Chee (2003)
This study focuses on the causes of high voluntary turnover in the finance department of Highlands International Resorts and Casinos(HIRC) Berhad, which is a public listed company,primary involved in business activities of leisure and hospitality, tours a